Aneurysm of the popliteal artery: Case report - (:unkn) unknown (My University, 2007)
Popliteal artery aneurysms lead to many dreadful conditions if left untreated. We report a case of a 63-year-old man who presented with a pain in the lower extremity as a result of a popliteal artery aneurysm. He underwent surgery through a posterior approach with saphenous vein graft interposition. The presentation, investigation and treatment of this condition is discussed.
Keywords: Aneurysm; Management; Popliteal artery